Autistic traits and internet gaming addiction in Chinese children: The mediating effect of emotion regulation and school connectedness. (September 2017) - Liu, Sha; Yu, Chengfu; Conner, Bradley T.; Wang, Suiping; Lai, Weiping; Zhang, Wei
Abstract: This report details an 18-month longitudinal study designed to investigate the influence of autistic traits' on internet gaming addiction (IGA) in children. A total of 420 Chinese children (220 boys, Mean age = 9.74 ± 0.45) participated in the research. Autistic traits were measured in the 4th grade and emotion regulation, school connectedness and IGA measured in both the 4th and 5th grades. After controlling for age, sex, and sensation seeking, results showed that autistic traits were related to decreased emotion regulation, which in turn was related to lower school connectedness, which was related to increased IGA. The results suggest that improving emotion regulation and school connectedness could reduce the risk of IGA. As a result, these findings may inform intervention and prevention programs targeting children with IGA, especially among those with high levels of autistic traits.